Comparative transcriptome analyses and CRISPR/Cas9-mediated functional study of Tfsdh1 reveal insights into the interaction between Tremella fuciformis and Annulohypoxylon stygium - Wang, Yuanyuan; Xu, Danyun; Hao, Mei; Ma, Aimin (Frontiers in Microbiology, 2026)
Tremella fuciformis, a famous edible and medicinal fungus, completes its life cycle in nature with the companion fungus Annulohypoxylon stygium. Although previous studies have initially explored the molecular mechanisms underlying this interaction, related pathways and genes in T. fuciformis remain poorly characterized. To address this, substrate-cultured samples were collected for RNA-seq. Differentially expressed genes (DEGs) in both T. fuciformis and A. stygium were identified and subjected to GO and KEGG annotation and enrichment analyses. Upregulated pathways were examined and DEGs associated with pentose metabolism were selected for pathway construction. One significantly upregulated gene, Tfsdh1 (gene_sp10002100.1), was chosen for further functional validation using CRISPR/Cas9 gene editing system, a method established in our laboratory. The results revealed that the DEGs are primarily involved in carbohydrate and amino acid metabolism. Upregulated pathways were related to carbon source metabolism and stress defense, demonstrating their importance in the fungal interaction. Putative pentose catabolic pathway and oxido-reductive pathway were constructed by integrating RNA-seq data with existing literature. Phenotypic analysis demonstrated that deletion of Tfsdh1 in T. fuciformis adversely affected mycelial growth rate, morphology, sorbitol utilization, SDH activity, and interaction with A. stygium. In conclusion, comparative transcriptome analyses provide novel insights to investigate the interaction between T. fuciformis and A. stygium. Functional research revealed that Tfsdh1 plays a critical role in sorbitol metabolism during the interaction, providing a foundation for further elucidating the molecular mechanisms of the interaction between these two fungi.